1992
DOI: 10.1111/j.1398-9995.1992.tb02385.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine‐induced inhibition of neutrophil chemotaxis and T‐lymphocyte proliferation in man

Abstract: Histamine inhibits in vitro human neutrophil chemotaxis and T-lymphocyte proliferation via H2 receptors. The aim of this study was to verify these inhibitory effects of histamine in man in vivo. Healthy volunteers were challenged with histamine by intravenous (1 mg), subcutaneous (1 mg) and inhalatory (2.4 mg) routes. Venous blood was taken before and at different times after challenge. Neutrophil chemotaxis was studied by the Boyden assay and T-lymphocyte proliferation by counting H3-thymidine incorporation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 17 publications
1
36
0
2
Order By: Relevance
“…Histamine, whose mast cells are the major storage site, is an attractive candidate as a dendritic cell modulator especially during early phases of the immune response. Histamine was reported to have immunosuppressive effects, such as inhibition of polymorphonuclear chemotaxis (23) and monocyte IL-12 secretion (24), as well as induction of IL-10 production (25). Interestingly, analysis of cytokine production by cultured LN cells after completion of DTH response indicate that increased production of IL-10 by mosquito bites was correlated with the presence of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine, whose mast cells are the major storage site, is an attractive candidate as a dendritic cell modulator especially during early phases of the immune response. Histamine was reported to have immunosuppressive effects, such as inhibition of polymorphonuclear chemotaxis (23) and monocyte IL-12 secretion (24), as well as induction of IL-10 production (25). Interestingly, analysis of cytokine production by cultured LN cells after completion of DTH response indicate that increased production of IL-10 by mosquito bites was correlated with the presence of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…These mediators are contained in intracellular WBC granules, and are released in a time-dependent manner as the WBCs deteriorate during storage [59]. It has been shown that at least some of these biologic response modifiers (histamine, eosinophil cationic protein, eosinophil protein X, TGF-β) may contribute to the development of immunosuppression and tissue damage by inhibition of neutrophils, cytotoxic T-cells and natural killer cells [60], [61], [62], [63].…”
Section: Immunosuppressionmentioning
confidence: 99%
“…reports have extensively documented the inhibitory effects of adenylate cyclase linked G protein-coupled receptor agonists on lymphocyte proliferation (16,19,21,35). To identify the molecular mechanism responsible for this effect, we first sought to determine whether Fsk, a potent adenylate cyclase activator, affects the proliferation of the human T-cell lines such as Kit 225 ( was due to an increase in cAMPi, cAMPi generation was measured using an ELISA.…”
Section: Forskolin-induced Campi Inhibits T-cell Proliferation and DImentioning
confidence: 99%